Bond Liquidity at the Oslo Stock Exchange - Bernt Arne Ødegaard (Norges Bank, 2017)
We characterize the liquidity of bond trading at the Oslo Stock Exchange (OSE). We use the complete history of bond prices quoted at the OSE from 1990 to 2016. We first characterize the market place, summarize trading grouped by type of issuers. The OSE can be characterized as a market place with a few bonds traded often, the rest traded seldom. The active bonds are Treasury securities, which typically trade on a daily basis. A second category of active bonds are covered bonds, a type of bond introduced as recent as 2008 (in the wake of the financial crisis). The remainder of bonds at the OSE are traded seldom. The activity of the bond market at the OSE has increased markedly in the post-2008 period. While Treasury securities remain the most active class, covered bonds has seen a marked increase in liquidity. We also see an increase in activity for the other bond groups. The number of bonds listed has doubled in the last ten years, with financial and industrial issuers increasing the most. The market had more than 3000 different bond issues active in the last five years. However, only half of these bonds trade more than five times a year. The second part of the paper investigates the feasibility of measuring liquidity in the Norwegian bond market. Is it possible to construct liquidity measures that are informative about the state of the Norwegian financial market? We calculate three different measures that can be calculated from daily data: Bid/Ask Spreads, the Amihud [2002] ILLIQ measure, and the Corwin and Schultz [2012] spread estimate from high/low prices. Except for Treasuries, the liquidity measures are hard to calculate due to limited trading interest. Of the three liquidity measures, the Corwin and Schultz measure seem to be the preferred, although the measures are clearly correlated. All measures show that aggregate bond market liquidity covary with slowdowns in the Norwegian economy, with liquidity worsening (trading costs/spreads increasing) around such events as the 1992 Banking Crisis and the 2008 Financial Crisis. We also compare estimates of trading costs for various types of bonds with equities, and find that the most expensive to trade is equities. Trading costs for corporate bonds are lower than equities, but higher than Treasury bonds, which is the category with lowest estimated transaction costs. This is contrary to the evidence from the US, and most European bond markets, where estimates of transaction costs for corporate bonds are much higher than trading costs for equities.
hdl:11250/2506377
Keywords: G10; G20; 330; Oslo Stock Exchange; Norway; bond markets; liquidity; trading costs